Anti‐Inflammatory and Anti‐Oxidative Nutrition in Hypoalbuminemic Dialysis Patients (AIONID) study: results of the pilot‐feasibility, double‐blind, randomized, placebo‐controlled trial. Issue 4 (20th September 2013) - Rattanasompattikul, Manoch; Molnar, Miklos Z.; Lee, Martin L.; Dukkipati, Ramanath; Bross, Rachelle; Jing, Jennie; Kim, Youngmee; Voss, Anne C.; Benner, Debbie; Feroze, Usama; MacDougall, Iain C.; Tayek, John A.; et al.
Abstract : Background: Low serum albumin is common and associated with protein‐energy wasting, inflammation, and poor outcomes in maintenance hemodialysis (MHD) patients. We hypothesized that in‐center (in dialysis clinic) provision of high‐protein oral nutrition supplements (ONS) tailored for MHD patients combined with anti‐oxidants and anti‐inflammatory ingredients with or without an anti‐inflammatory appetite stimulator (pentoxifylline, PTX) is well tolerated and can improve serum albumin concentration. Methods: Between January 2008 and June 2010, 84 adult hypoalbuminemic (albumin <4.0 g/dL) MHD outpatients were double‐blindly randomized to receive 16 weeks of interventions including ONS, PTX, ONS with PTX, or placebos. Nutritional and inflammatory markers were compared between the four groups. Results: Out of 84 subjects (mean ± SD; age, 59 ± 12 years; vintage, 34 ± 34 months), 32 % were Blacks, 54 % females, and 68 % diabetics. ONS, PTX, ONS plus PTX, and placebo were associated with an average change in serum albumin of +0.21 ( P  = 0.004), +0.14 ( P  = 0.008), +0.18 ( P  = 0.001), and +0.03 g/dL ( P  = 0.59), respectively. No related serious adverse events were observed. In a predetermined intention‐to‐treat regression analysis modeling post‐trial serum albumin as a function of pre‐trial albumin and the three different interventions (ref = placebo), only ONS without PTX was associated with a significant albumin rise (+0.17 ± 0.07 g/dL, P  = 0.018). Conclusions: In this pilot‐feasibility, 2 × 2 factorial, placebo‐controlled trial, daily intake of a CKD‐specific high‐protein ONS with anti‐inflammatory and anti‐oxidative ingredients for up to 16 weeks was well tolerated and associated with slight but significant increase in serum albumin levels. Larger long‐term controlled trials to examine hard outcomes are indicated. Electronic supplementary material: The online version of this article (doi:10.1007/s13539‐013‐0115‐9) contains supplementary material.